Violence Syndicale Estudiantine Dans Les Universités Publiques De Côte d’Ivoire : Perceptions Et Enjeux - Diarassouba Ibrahima (European Scientific Journal, ESJ, 2017)
During the decades 1990-2010 that followed the introduction of the multiparty system in 1990, the educational environment in particular the academic institutions in Côte d’Ivoire were greatly affected by the recurrence of student union violence. With the "new departure" which marks a new dynamics of the universities by a break with the practices which have begun their normal functioning based on the effect of giving them their luster from before, we have noted the survival of this violence. The aim of this study is to discover, on the one hand, the perception that student unionists have about violence and, on the other hand, to analyze the stakes involved in the systematic use of violence by these unionized students during the two decades of 1990- 2010 to understand the survival of this phenomenon in the context of "new departure". To achieve this, we have chosen the six (06) unions that have marked the history of student violence the more during the period 1990-2010. With the aid of semi-directive interviews, we have collected the data which reveal the perception that violence for the trade unions is a legitimate and legal act according to their own statute and internal regulations. It shows that there is a congenital link between trade unionism and politics. Therefore, trade unionism cannot be exercised without politics. Under the stakes, it appears that violence is an indicator of trade union dynamism for political positioning; that it confers power by the domination of public spaces such as universities.